2012
DOI: 10.1093/nar/gks1215
|View full text |Cite
|
Sign up to set email alerts
|

INTERFEROME v2.0: an updated database of annotated interferon-regulated genes

Abstract: Interferome v2.0 (http://interferome.its.monash.edu.au/interferome/) is an update of an earlier version of the Interferome DB published in the 2009 NAR database edition. Vastly improved computational infrastructure now enables more complex and faster queries, and supports more data sets from types I, II and III interferon (IFN)-treated cells, mice or humans. Quantitative, MIAME compliant data are collected, subjected to thorough, standardized, quantitative and statistical analyses and then significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
796
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 749 publications
(853 citation statements)
references
References 34 publications
26
796
0
Order By: Relevance
“…5F, 5G and data not shown). The total number of IFN-g/CD107a coproducers following ex vivo GP [33][34][35][36][37][38][39][40][41] peptide restimulation was consistently, but not significantly higher, in DTA-1-treated animals (Fig. 5F).…”
Section: Agonistic Anti-gitr Augments Cd8 T Cell Responses To Lcmv Wimentioning
confidence: 90%
See 2 more Smart Citations
“…5F, 5G and data not shown). The total number of IFN-g/CD107a coproducers following ex vivo GP [33][34][35][36][37][38][39][40][41] peptide restimulation was consistently, but not significantly higher, in DTA-1-treated animals (Fig. 5F).…”
Section: Agonistic Anti-gitr Augments Cd8 T Cell Responses To Lcmv Wimentioning
confidence: 90%
“…Splenocytes were stained with tetramer and surface stain Abs for 1 h at 4˚C, after which cells were washed thoroughly and fixed in 4% paraformaldehyde for 30 min at 4˚C. For intracellular cytokine staining, splenocytes were cultured in complete medium with brefeldin A and monensin (BD Biosciences; catalog 554715) with 1 mg/ml H-2D b -restricted LCMV NP 396-404 , GP [33][34][35][36][37][38][39][40][41] , or GP 276-286 (Anaspec, Fremont, CA) and 0.5 mg/ml anti-CD107a or IgG1 isotype control (BD Biosciences) for 5 h, or 4 mg/ml I-A b -restricted LCMV GP 61-80 with 20 U/ml murine rIL-2 (eBioscience) for 5 h. Cells were then surface stained, fixed, permeabilized (BD Biosciences), and stained for intracellular cytokine production.…”
Section: Surface and Intracellular Cytokine Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…S2 A and B), we first evaluated the impact of this CLR in a global and unbiased manner through genomewide transcriptome analysis of bone marrow-derived DCs from WT and DCIR-KO animals before and during M. tuberculosis infection. Functional gene set enrichment analysis (GSEA) and interrogation of the Interferome database (21) revealed that a significant fraction of genes, which were down-regulated in DCIR-KO DCs compared with WT cells, was dependent on type I IFN and/or included genes involved in defense to viruses (SI Appendix, Fig. S3 and Fig.…”
Section: Dcir Expressionmentioning
confidence: 99%
“…Bioinformatic approaches have led to the identification of IFN-inducible gene signatures (38)(39)(40), although the precise function of individual IRGs in an immune response is still being elucidated (39). This IFN gene signature is traditionally referred to as the "antiviral state" (41) (45).…”
Section: Type I Ifn Signaling Pathwaymentioning
confidence: 99%